Local Determinants of Crime: Do Military Bases Matter? - Alfredo R. Paloyo; Colin Vance; Matthias Vorell (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Using a unique panel dataset, we estimate the impact of the military base realignments and closures (BRACs) in Germany on the intensity of criminal activity surrounding the base. We use a fi xed-eff ect model to account for time-invariant unobservables in our panel of 298 military bases for the period 2003-2007. We also take advantage of geographic information system software to mitigate estimation issues arising from the spatial nature of the dataset. Estimation results are presented for total crime and four other subcategories: breaking and entering, automobile-related crime, violent crime, and drug-related crime. The estimates indicate that there is no eff ect of BRACs on criminal activity surrounding the base. We also confi rm existing fi ndings in the literature on the determinants of crime. – – Mithilfe von Paneldaten untersuchen wir den Einfluss von Militärstandorten auf Kriminalität in den sie umgebenden Regionen für die Jahre 2003 bis 2007. Die Restrukturierung der Bundeswehr in diesem Zeitraum ermöglicht uns die kausale Identifikation durch ein natürliches Experiment. Durch die Benutzung eines Geodatensystems und die Bildung von Pufferzonen um die Basen berücksichtigen wir besonders die kleinräumige Natur der Daten. Wir finden keinerlei Einfluss der Bundeswehr auf Kriminalitätsraten in den umliegenden Gemeinden. Ansonsten bestätigen unsere Ergebnisse existierende Befunde der Kriminalitätsforschung in Deutschland.
Keywords: H56; K42; R19; 330; armed forces; BRAC; deviant behavior; geographic information system